Report on the application of the Regional Strategy for the Implementation in Latin America and the Caribbean of the Madrid International Plan of Action on Ageing (ECLAC [Santiago]CL, 2007)
Presents and analyzes the available information on the process of population ageing, the status of the older adult population and the advances made by countries in applying the Regional Strategy.
Bibliography: 137-144